PELATIHAN PENGGUNAAN PERANGKAT PEMBELAJARAN ONLINE BAGI GURU-GURU MAN DI KABUPATEN JOMBANG - Mariana Ulfah Hoesny; Yani Ratnawati; Lia Agustina; Aly Imron (JPM PAMBUDI, 2021)
The use of online learning tools has been urgent due to covid-19 pandemic. The tools have become primary needs in teaching and learning especially in English teaching. This program aimed at conducting training and workshop to use online learning tools for English teachers of Madrasah Aliyah in Jombang regency, East Java. The workshop was done via zoom meeting because offline meeting was not allowed during the pandemic. The first topic presented in the established workshop was about how technology transform education. The next topics were more specific ones; they were about utilizing online learning tools and project based learning to teach the four skills in English. There were 148 participants attending the workshop. According to te participants, the most interesting topics during the workshop were about the use of story jumper to teach writing and how to make podcast to teach speaking.